Modeling the effects of heating temperature, pH, and Natamycin Concentration on the thermal inactivation of a resistant spoilage yeast - Anapi, Gerieka Ramos
This study was conducted to characterize and quantify the effects of intrinsic and extrinsic fruit juice properties, namely heating temperature (T), pH, and natamycin concentration (NAT) on the thermal reduction times (D T values) of a resistant yeast strain. In the first phase of the study, a two-stage screening was conducted: 17 yeast strains were first treated at 55°C for 5 minutes in Yeast Extract Peptone Glucose Broth, then the 6 most resistant were tested in orange juice at 50–60°C to determine their D T and z-values and identify the most heat-resistant strain. In the second phase, Central Composite Rotatable Design of Experiment (CCRD) was employed to identify simulated fruit juice (SFJ) formulations with specific T, pH, and NAT combinations that served as a suspending medium for the target microorganism. Response Surface Methodology (RSM) was used to establish a model that characterized and quantified the effects of the key variables on the DT values, which were determined using the model-fitting method. Lastly, application of the developed predictive model was done in Philippine native lemon juice drink (PLD) as a real fruit juice system. Results showed that Pichia fermentans BFE38 exhibited the greatest (p < 0.05) DT values at 50–55°C. However, the test isolate with the greatest z-value (p < 0.05) was found to be Pichia anomala (BIOTECH 2205), which was identified as the target microorganism for the predictive model building. RSM results showed that the individual linear of all variables (T, pH, and NAT), individual quadratic (T²), and factor interactions (pH × T) were found to significantly influence thermal inactivation (p < 0.05). Predictive performance indices (Af and Bf) were within the acceptable values. Both predicted and actual pasteurization treatments using the full model achieved microbial reductions compliant with safety standards while maintaining stable physicochemical and color attributes.